Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^4+\left(x-4\right)^4-82\)
\(=\left(x^4-1\right)+\left[\left(x-4\right)^4-81\right]\)
\(=\left(x^2+1\right)\left(x^2-1\right)+\left[\left(x^2-4x+4-9\right)\left(x^2-4x+4+9\right)\right]\)
\(=\left(x^2+1\right)\left(x+1\right)\left(x-1\right)+\left(x^2-4x-5\right)\left(x^2-4x+13\right)\)
\(=\left(x^2+1\right)\left(x+1\right)\left(x-1\right)+\left(x^2+x-5x-5\right)\left(x^2-4x+13\right)\)
\(=\left(x^2+1\right)\left(x+1\right)\left(x-1\right)+\left(x+1\right)\left(x-5\right)\left(x^2-4x+13\right)\)
\(=\left(x+1\right)\left[\left(x^2+1\right)\left(x-1\right)+\left(x-5\right)\left(x^2-4x+13\right)\right]\)
\(=\left(x+1\right)\left(x^3-x^2+x-1+x^3-4x^2+13x-5x^2+20x-65\right)\)
\(=\left(x+1\right)\left(2x^3-10x^2+34x-66\right)\)
\(=\left(x+1\right)\left(2x^3-6x^2-4x^2+12x+22x-66\right)\)
\(=\left(x+1\right)\left[2x^2\left(x-3\right)-4x\left(x-3\right)+22\left(x-3\right)\right]\)
\(=\left(x+1\right)\left(x-3\right)\left(2x^2-4x+22\right)\)
1 ) \(x^5+x+1\)
\(=\left(x^5-x^2\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x^3-1\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
b ) \(x^8+x^4+1\)
\(=\left(x^8+2x^4+1\right)-x^4\)
\(=\left(x^4+1\right)^2-\left(x^2\right)^2\)
\(=\left(x^4-x^2+1\right)\left(x^4+x^2+1\right)\)
x^5+x^4+1=x^5+x^4+x^3-x^3-x^2-x+x^2+x+1=x^3(x^2+x+1)-x(x^2+x+1)+x^2+x+1=(x^3-x+1)(x^2+x+1)
\(x^5+x^4+1\)
\(=x^3\left(x^2+x+1\right)-x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^3-x+1\right)\left(x^2+x+1\right)\)
Ta có : x5 - x4 + x4 - x3 - x4 + x3 - x2 + x2 - x + x - 1
= x4(x - 1) + x3(x - 1) - x3(x - 1) - x2(x - 1) + x2(x - 1) + (x - 1)
= (x4 + x3 - x3 - x2 + x2 + 1) (x - 1)
= (x4 + 1)(x - 1)
khó nhỉ